Systematic review of SLC4A11, ZEB1, LOXHD1, and AGBL1 variants in the development of Fuchs’ endothelial corneal dystrophy - Tsedilina, Tatiana Romanovna; Sharova, Elena; Iakovets, Valeriia; Skorodumova, Liubov Olegovna (Frontiers in Medicine, 2023)
Introduction The pathogenic role of variants in TCF4 and COL8A2 in causing Fuchs’ endothelial corneal dystrophy (FECD) is not controversial and has been confirmed by numerous studies. The causal role of other genes, SLC4A11, ZEB1, LOXHD1, and AGBL1, which have been reported to be associated with FECD, is more complicated and less obvious. We performed a systematic review of the variants in the above-mentioned genes in FECD cases, taking into account the currently available population frequency information, transcriptomic data, and the results of functional studies to assess their pathogenicity. Methods Search for articles published in 2005–2022 was performed manually between July 2022 and February 2023. We searched for original research articles in peer-reviewed journals, written in English. Variants in the genes of interest identified in patients with FECD were extracted for the analysis. We classified each presented variant by pathogenicity status according to the ACMG criteria implemented in the Varsome tool. Diagnosis, segregation data, presence of affected relatives, functional analysis results, and gene expression in the corneal endothelium were taken into account. Data on the expression of genes of interest in the corneal endothelium were extracted from articles in which transcriptome analysis was performed. The identification of at least one variant in a gene classified as pathogenic or significantly associated with FECD was required to confirm the causal role of the gene in FECD. Results The analysis included 34 articles with 102 unique ZEB1 variants, 20 articles with 64 SLC4A11 variants, six articles with 26 LOXHD1 variants, and five articles with four AGBL1 variants. Pathogenic status was confirmed for seven SLC4A11 variants found in FECD. No variants in ZEB1, LOXHD1, and AGBL1 genes were classified as pathogenic for FECD. According to the transcriptome data, AGBL1 and LOXHD1 were not expressed in the corneal endothelium. Functional evidence for the association of LOXHD1, and AGBL1 with FECD was conflicting. Conclusion Our analysis confirmed the causal role of SLC4A11 variants in the development of FECD. The causal role of ZEB1, LOXHD1, and AGBL1 variants in FECD has not been confirmed. Further evidence from familial cases and functional analysis is needed to confirm their causal roles in FECD.